Implementation of Design Thinking and Lean Startup Method in New Product Development of Natural Skincare from Cascara: Study Case of Kamala (Journal of Innovation, Business and Entrepreneurship, 2020)
Beauty has become a necessity in this era, especially for women. The trend for beauty products is now moving to natural ingredients, as customers are scared of chemicals. As a result of seeing the positive opportunity and promising market growth in natural skincare, Biesha - a biotechnology startup in Bandung emerges to develop new products in the beauty industry with the main material from cascara. Based on the study, it shows that the root cause that beauty value in the product is not delivered yet as customer expectation. We see the potency that cascara can be developed into new products in the form of skincare. This is based on the idea of supplementing the skin from the outside is gaining more impact (Ascenso et al., 2013; Carneiro et al., 2011). Thus, this research was aimed to gain insights from the implementation of new product development using design thinking to contribute to new solutions that meet the most critical consumer needs. Based on the data collected using a semi-structured interview, the researcher found out some insights about the skincare product from cascara that already meets the needs and requirements of the persona which is called cascara serum. While the lean startup approach is used to do validated learning after the Minimum Viable Product (MVP) is created. This step is aimed to establish the consumers by the time the product is ready for widespread distribution. The researcher validated the value that influences the choice intentions of cascara serum by using Structural Equation Modelling (PLS-SEM). It was found that the choice intentions significantly affected conditional value then followed by the functional value of benefit and functional value of price. Other than that, the researcher also measures the growth hypothesis of MVP by using Net Promoter Score (NPS) to know how many people would recommend the product. The result of NPS shows that the ‘passive’ gets a greater score than the ‘promoter’. The insights from the implementation of design thinking and lean startup methods then used to create the recommendation of marketing strategies to be implemented in cascara serum.Keywords: New product development, natural skincare, design thinking, lean startup